A major review on tribology-based materials - Norazlianie, Sazali; Ahmad Shahir, Jamaludin; Nor Hasrul Akhmal, Ngadiman (Akademi Baru, 2020)
The utilization of advanced material in a diverse area can enhance the performance and quality of material engineering. Consequently, tribology testing becomes a demand in the industry such as construction, aviation, and automotive because of the widespread use of polymer-based natural fiber composites for their components and parts. This paper includes the discussion of each composites material that has different wear and sliding friction that required a different technique to encounter based on the ASTM standards by simulating under the real-time. The use of different materials demonstrates the wear and friction behavior and their potential for tribology engineering applications of the material are discussed in this review paper.